ORGANIZATIONAL CULTURE, WORK ENVIRONMENT, AND SELF-EFFICACY TO GEN Z’S JOB SATISFACTION - Sanlia, Vera; Turangan, Joyce A. (International Journal of Application on Economics and Business, 2023)
Human resources are needed to carry out daily activities, such as engaging in interactions and communication within a community (work environment, organization, and other activities). Based on previous research, there are still differences in research findings. This study aims to find the effect of organizational culture, work environment, and self-efficacy on Gen Z’s job satisfaction. Data was collected using a questionnaire with a Google Form which was distributed via social media. The total number of respondents of this study is 130, domiciled in Jakarta with the aged around 18-25 years and have at least worked for 1 year. The data were examined using the SmartPLS 4.0 application. The results of the study show through hypothesis testing that all the independent variables have a positive and significant effect on Gen Z’s job satisfaction.